2019
DOI: 10.1029/2019ea000873
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Six Lightning Parameterizations in CAM5 and the Impact on Global Atmospheric Chemistry

Abstract: We present simulations performed with six lightning parameterizations implemented in the Community Atmosphere Model (CAM5). The amount of lightning-produced nitrogen oxides (LNO x ) by the various schemes considered is estimated. We provide some insight on how the lightning NO injected in the atmosphere influences the global concentrations of key chemical species such as OH, HO 2 , H 2 O 2 , NO x , O 3 , SO 2 , CO, and HNO 3 . The vertical global averaged densities of HO 2 , H 2 O 2 , CO, and SO 2 are depleted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 102 publications
1
37
0
Order By: Relevance
“…The main sink of HONO 2 is surface deposition. Several modeling studies (e.g., Søvde et al, 2011;Gottschaldt et al, 2013;Archibald et al, 2020) have investigated the impact of including channel R12b and shown that it could lower tropospheric ozone production rates considerably (20%). Urgent laboratory studies are required to corroborate the HONO 2 forming channel R12b.…”
Section: The Photochemical Formation Mechanism Of Tropospheric Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…The main sink of HONO 2 is surface deposition. Several modeling studies (e.g., Søvde et al, 2011;Gottschaldt et al, 2013;Archibald et al, 2020) have investigated the impact of including channel R12b and shown that it could lower tropospheric ozone production rates considerably (20%). Urgent laboratory studies are required to corroborate the HONO 2 forming channel R12b.…”
Section: The Photochemical Formation Mechanism Of Tropospheric Ozonementioning
confidence: 99%
“…The formation of HONO 2 as a product from the reaction between HO 2 þ NO (Butkovskaya et al, 2005(Butkovskaya et al, , 2007(Butkovskaya et al, , 2009 has been shown in modeling studies to have a potentially significant impact on the tropospheric ozone burden (Søvde et al, 2011;Gottschaldt et al, 2013;Archibald et al, 2020). Independent laboratory studies are required to verify this channel in the reaction and to better understand the role of water vapour in this and other peroxy radical reactions.…”
Section: Outstanding Science Questions Related To Understanding the Omentioning
confidence: 99%
“…The higher observed LNO x in Allen et al () and Bucsela et al () may be a combined result of differences in WWLLN detection efficiency correction, which is larger than for ENTLN, as well as the stroke versus flash biases discussed earlier in this paper. Finally, Gordillo‐Vázquez et al () performed a global modeling study using various parameterizations for lightning to determine that LNO x was on average between 310–441 mol·flash −1 ; however, oceanic lightning is known to have larger peak currents than continental lightning (Nag & Cummins, ), which should result in higher LNO x .…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, there are reports that CG and IC strokes/flashes produce similar amounts of NO x . From a purely electrostatic analysis of the charge neutralized by a lightning flash, Gallardo and Cooray (1996) concluded that CG and IC flashes dissipate similar amounts of energy, which, assuming LNO x scales linearly with energy per flash, produced comparable LNO x . Cooray et al (2009) predicted that CG and IC flashes both produced 3.3-mol NO per coulomb of charge neutralized in a theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis suggests that LCC-lightning occurrence over Europe can be parameterized in atmospheric models using meteorological variables as proxy. Such a parameterization can be used in future studies to improve the modeling of fire occurrence and its atmospheric emissions in such models, where different atmospheric variables are used as proxies for the occurrence of lightning [e.g., (Tost et al, 2007;Murray et al, 2012;Gordillo-Vázquez et al, 2019)]. The launch of the Meteosat Third Generation (MTG) geostationary satellites of the EUropean organization for the exploitation of METeorological SATellites (EUMETSAT) in 2022 will provide for the first time a continuous monitoring of the occurrence of lightning flashes and fires in Europe and Africa through the instruments Lightning Imager (LI) and Flexible Combined Imager (FCI) from 2023, after the commissioning phase (Stuhlmann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%